Transparency of machine-learning in healthcare: the GDPR and European health law - Mourby, M; O'Cathaoir, K; Collin, CB (Elsevier, 2021)
Machine-learning (‘ML’) models are powerful tools which can support personalised clinical judgments, as well as patients’ choices about their healthcare. Concern has been raised, however, as to their ‘black box’ nature, in which calculations are so complex they are difficult to understand and independently verify. In considering the use of ML in healthcare, we divide the question of transparency into three different scenarios: 1) Solely automated decisions. We suggest these will be unusual in healthcare, as Article 22(4) of the General Data Protection Regulation presents a high bar. However, if solely automatic decisions are made (e.g. for inpatient triage), data subjects will have a right to ‘meaningful information’ about the logic involved.